Ellappa Nāvalaravarkaḷ iyaṟṟiyaruḷiya Tiruvaruṇaik kalampakam - Irāmaliṅkam Piḷḷai, Ve., 1888-1972 (SAMP early 20th-century Indian books project, 1934)
Commentary on Tiruvaruṇaik kalampakam, hymns in praise of Siva, Hindu deity, enshrined at Tiruvannāmalai, by Ellappa Navalar.